The Blue-Green Infrastructure Paradigm in India: Landscape Design Proposal for transforming the Mahalaxmi Racecourse into a Resilient City Park, Mumbai (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Accelerated urbanization in megacities around the world has resulted in an acute shortage of open spaces, the living infrastructure that modulates climate and creates community. Dense coastal cities in India e.g., Mumbai has experienced intentional paving over of the natural greens overtime bringing down already low open space per capita levels while increasing the risk of urban hydrological disasters. Current city stormwater systems that are designed on traditional discharge-based engineering are ill-equipped to handle the sudden surge of monsoon rainfall events. There is an urgent need to reimagine grey infrastructure in urban areas as hybrid green-blue landscapes. The objective of this paper is to provide landscape design strategies to transform Mumbai’s 120-acre Mahalaxmi Racecourse land parcel into a high performance, resilient public open space through application of the Sponge City concept. The design workflow consists of an initial bio-physical overlayed site analysis which determines that the Mahalaxmi Racecourse is a low-lying basin that currently collects runoff from surrounding urban catchment. After establishing opportunities for site-scale stormwater management beyond basic park aesthetics the project moves to formulate a design basis rooted in Nature-based Solutions (NbS) that can detain a 5-year peak rainfall event across most of the central part as marshes and ponds thereby lowering site’s current runoff coefficient of 0.85 to 0.45. Design guidelines are developed based on desired engineered landscape outcomes such as a Native Arboretum Core planned, and Riparian Bio-Filtration Spine that naturally purifies urban runoff through root-zone Phyto-treatment. Additionally, network-level design strategy such as the incorporation of an underground transit under-pass and an elevated walkway loop was proposed to overcome the sites disconnect from adjacent railway and major road grids respectively. Operational sustainability was designed into the project through implementation of a Closed-loop Stewardship Model that segments larger site into revenue-generating Active Cells that subsidize maintenance operations of less used Ecological Core Cells. The speculative Master Plan effectively unlocks the enormous potential of underutilized urban mega voids and provides a replicable template for transforming them into equitable, productive, self-sustaining infrastructure that enhances urban resilience and increases public access in cities of the Global South.